Pulmonary Apergillosis (Reporting by two cases) - Aguilar Celi, Polinestor (1960)
We report on two cases of pulmonary aspergillosis found in Chico Bravo Sanitarium, one of them in an autopsy case and the other in a pulmonary surgical specimen.